2017
DOI: 10.1007/s12325-017-0575-y
|View full text |Cite|
|
Sign up to set email alerts
|

Gluten and Aluminum Content in Synthroid® (Levothyroxine Sodium Tablets)

Abstract: IntroductionInquiries from healthcare providers and patients about the gluten and aluminum content of Synthroid® (levothyroxine sodium tablets) have increased. The objective of this study was to measure and evaluate the gluten content of the raw materials used in the manufacturing of Synthroid. Additionally, this study determined the aluminum content in different strengths of Synthroid tablets by estimating the amount of aluminum in the raw materials used in the manufacturing of Synthroid.MethodsGluten levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, most studies showing better absorption with soft gel or liquid LT4 formulations compared with tablets were published after the ATA guidelines were released. As a result, there are no specific recommendations for the use of such formulations in these circumstances, but it has been suggested that they may be useful in patients with allergies or side effects to the excipients found in some LT4 tablets (e.g., lactose in Synthroid) [3, 5456].…”
Section: Bioequivalence and Interchangeabilitymentioning
confidence: 99%
“…However, most studies showing better absorption with soft gel or liquid LT4 formulations compared with tablets were published after the ATA guidelines were released. As a result, there are no specific recommendations for the use of such formulations in these circumstances, but it has been suggested that they may be useful in patients with allergies or side effects to the excipients found in some LT4 tablets (e.g., lactose in Synthroid) [3, 5456].…”
Section: Bioequivalence and Interchangeabilitymentioning
confidence: 99%
“…Intolerance to synthroid in our patient could be due to gluten content, although she was unaware of gluten sensitivity in her regular diet. 10 Also, different levothyroxine preparations may exhibit differences in the bioequivalence. 7 As the concern was of intolerability rather than the bioavailability, the decision was made to equate the dose of eltroxin early.…”
Section: Discussionmentioning
confidence: 99%